Ukuran Perusahaan, Profitabilitas, Dewan Komisaris Dan Komite Audit Terhadap Pengungkapan Corporate Social Responsibility - Viorentina, Sheren; Febriany , Novita (Prodi Akuntasi, Fakultas Bisnis dan Akuntansi Unika Musi Charitas, 2022)
This study was used to examine the relationship between firm size, profitability, the board of commissioners and the audit committee on the disclosure of corporate social responsibility. The object of this research is to determine the relevance of the results of this study, which aims to identify the influence between the factors that encourage the disclosure of corporate social responsibility. The higher the factors used, the better the disclosure of corporate social responsibility will be. The existence of factors such as company size, profitability, and audit committee will encourage better disclosure of corporate social responsibility.